Dynamic modelling and simulation of a manual transmission based mild hybrid vehicle. (June 2017) - Awadallah, Mohamed; Tawadros, Peter; Walker, Paul; Zhang, Nong
Highlights: Study the control of mild hybrid vehicles equipped with manual transmissions. Torque hole compensation achieved with the use of the secondary power source. Vibration dose value demonstrates improved shift quality of the mild hybrid vehicle. Abstract: This paper investigates the development of a mild hybrid powertrain system through the integration of a conventional manual transmission equipped powertrain and a secondary power source in the form of an electric motor driving the transmission output shaft. The primary goal of this paper is to study the performance of partial power-on gear shifts through the implementation of torque hole filling by the electric motor during gear changes. To achieve this goal, mathematical models of both conventional and mild hybrid powertrain are developed and used to compare the system dynamic performance of the two systems. This mathematical modelling is used to run different simulations for gear-shift control algorithm design during system development, allowing us to evaluate the achievable performance and its dependency on system properties. The impact of motor power on the degree of torque hole compensation is also investigated, keeping in mind the practical limits to motor specification. This investigation uses both the output torque, vehicle speed as well as vibration dose value to evaluate the quality of gearshifts at different motor sizes. Results demonstrate that the torque hole may be eliminated using a motor power of 50 kW. However, the minimum vibration dose value during gear change is achieved using a peak power of 16–20 kW. Graphical abstract: